Panama : Report on the Observance of Standards and Codes-Data Module; Response by the Authorities; and Detailed Assessments Using the Data Quality Assessment Framework. (IMF Staff Country Reports; Country Report ;, 2006)
Panama has a well-developed macroeconomic statistical system, and the government recognizes the importance of good statistics for policy and investment decisions. All statistical agencies are committed to further statistical progress by promoting implementation of the National Strategy for Statistical Development (NSSD). Executive Directors recommend that Panama should proceed with the amendment to the Law of the Controller General aimed at creating the National Institute of Statistics, and implement the annual supply and use framework to investigate discrepancies and improve consistency.